Problems Of Copyright Protection For Artificial Intelligence (AI) Works: A Study Of Legal Voids In Viral Cases Of Digital Creators - Anisa, Anisa; Septia, Sya’baniatie Ninda (Fakultas Syariah UIN Antasari, 2025)
Advances in artificial intelligence (AI) technology, particularly generative AI, have produced digital works that resemble human creations. However, Law Number 28 of 2014 on Copyright does not expressly regulate the legal status of AI-generated works or human contributions through prompts, resulting in a legal voids. This research examines the problem of copyright protection for AI-produced works from the perspective of Indonesian law. The discussion focuses on the legal status of prompts as expressions of ideas, the role of creators within the current legal framework, and the urgency of reforming the Copyright Law to face digital era challenges. This urgency is underscored by the growing number of cases involving unauthorized commercial use of AI works, such as the viral case between independent creator Noxxa and game company Garena. This study employs a qualitative approach using a normative juridical method, analyzing relevant laws in Indonesia and several other countries. The findings indicate that although AI-generated works are not directly protected, human contributions through original prompts can fulfill the requirement of originality and deserve copyright protection. Therefore, legal reform is needed to accommodate technological developments and ensure fair, proportional protection for works involving AI.